The influence of company size on its internationalization capacity: a comprehensive view on Portugal - Fernandes, Joel Barros; Albuquerque, Eduardo Barbas; da Silva, Amândio F. C. (Business: Theory and Practice, 2022)
In the competitive environment that companies operate today, there is a need to adopt internationalization strategies to enable consolidation in diversified markets. The internationalization process is part of a relevant strategy for companies, has several implications and is influenced by innumerable specific aspects, namely by the behavior of companies, by their culture and structure, as well as by their leadership, but it is on the organization structure that we find one of the most relevant features: the dimension (size) of companies. Based on a qualitative methodology, we interviewed managers of the furniture manufacturing industry. We concluded that companies value increase in size; nevertheless, for cultural reasons, they are still resistant to such an increase. For increasing their size, companies value several instruments, such as: strategic alliances/corporate cooperation; fusions and acquisitions; and risk capital interventions. This work is an eye opener about the need to educate and train entrepreneurs in the Portuguese industrial sector and to bring about an awareness of the benefits of formation, training, expansion and diversification in order to be able to compete on a global basis.